Clinical and Radiographic Assessment of Cases Referred to Endodontic Surgery - Brabara Babić; Janja Barun; Silvana Jukić Krmek; Ana Kotarac Knežević; Ivan Salarić; Ana Ivanišević Malčić (University of Zagreb. School of Dental Medicine, 2019)
Objective: The objective of the study was to assess the quality of root canal fillings of cases referred to endodontic surgery using preoperative radiographs and correlate it with endodontic surgery treatment decision. The objective was also to analyse clinical symptoms and size of periapical lesions on radiographs and correlate them with treatment decisions including non-surgical retreatment, endodontic surgery and extraction. Material and Methods: A questionnaire was composed to record the data. Eighty-six patients with 109 teeth, who were referred to endodontic surgery, participated in the research. The quality of root canal filling was assessed according to its homogeneity and filling length on digital radiographs. The data were analyzed using χ2-test and t-test. Results: Of the teeth referred to endodontic surgery, 97.2% were treated by a general practice dentist, endodontic retreatment was attempted in 20.6%, and root canal filling was homogeneous and within 1 mm from the apex in 21.6%. Endodontic surgery, retreatment, extraction and no treatment were selected in 90.1%, 5.4%, 1.8% and 2.7% of the cases, respectively. Conclusions: Low percentage of adequate root canal fillings and high percentage of endodontic surgery decisions suggest that there is a need to increase awareness of non-surgical retreatment options.